Pharmacist Counseling In Hypertensive Patients - Setyaningsih, Ike Budi; Hapsari, Indri; Genatrika, Erza (Syntax Corporation, 2025)
Hypertension is a major public health concern, contributing significantly to morbidity and mortality worldwide. Poor adherence to antihypertensive medications and lack of patient knowledge remain critical challenges in hypertension management. Pharmacists play a vital role in addressing these issues through counseling and patient education. This study aims to analyze the impact of pharmacist counseling on medication adherence, patient knowledge, and blood pressure control among hypertensive patients. A literature review was conducted, utilizing peer-reviewed research articles published between 2019 and 2025 from databases such as PubMed, Scopus, ScienceDirect, and Google Scholar. Studies focusing on pharmacist counseling interventions in hypertension management were included, while duplicate or non-relevant studies were excluded. Data analysis followed a qualitative framework, including data reduction, data presentation, and conclusion drawing to identify significant patterns and trends. The results indicate that pharmacist-led counseling improves medication adherence, enhances patients' understanding of hypertension management, and contributes to better blood pressure control. Patients receiving pharmacist counseling demonstrate higher adherence rates, greater awareness of their condition, and a significant reduction in both systolic and diastolic blood pressure levels. Furthermore, pharmacist interventions promote lifestyle modifications, such as dietary adjustments, increased physical activity, and smoking cessation, further contributing to improved hypertension management. Despite these positive outcomes, challenges remain in implementing pharmacist counseling effectively due to healthcare system limitations, patient-related barriers, and resource constraints. This study highlights the need for stronger integration of pharmacists in hypertension care and further research into the long-term impact of pharmacist-led interventions.